2018
DOI: 10.1002/lno.11110
|View full text |Cite
|
Sign up to set email alerts
|

Cable bacteria promote DNRA through iron sulfide dissolution

Abstract: Cable bacteria represent a newly discovered group of filamentous microorganisms, which are capable of spatially separating the oxidative and reductive half-reactions of their sulfide-oxidizing metabolisms over centimeter distances. We investigated three ways that cable bacteria might interact with the nitrogen (N) cycle: (1) by reducing nitrate through denitrification or dissimilatory nitrate reduction to ammonium (DNRA) within their cathodic cells; (2) by nitrifying ammonium within their anodic cells; and (3)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
26
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 44 publications
(27 citation statements)
references
References 60 publications
1
26
0
Order By: Relevance
“…Similar partitioning of the two dissimilative NO 3 − -reducing processes, with a relatively large contribution of DNRA has been observed in a wide range of environments, particularly in reduced sediments with high organic matter content and comparatively low nitrate levels (Burgin and Hamilton, 2007;Dong et al, 2011). The contribution of DNRA to total NO 3 − reduction can be particularly important in both estuarine sediments (∼5-91%; An and Gardner, 2002;Megonigal et al, 2004;Gardner et al, 2006;Burgin and Hamilton, 2007;Dong et al, 2009;Giblin et al, 2013;Roberts et al, 2014;Plummer et al, 2015;Kessler et al, 2019) and freshwater lake sediments (∼3-50%; Nizzoli et al, 2010;Wenk et al, 2014;Robertson and Thamdrup, 2017). Yet, the natural variability in these studied environments is quite high.…”
Section: Discussion Denitrification Versus Dnra In Lake Lugano Sedimentssupporting
confidence: 52%
“…Similar partitioning of the two dissimilative NO 3 − -reducing processes, with a relatively large contribution of DNRA has been observed in a wide range of environments, particularly in reduced sediments with high organic matter content and comparatively low nitrate levels (Burgin and Hamilton, 2007;Dong et al, 2011). The contribution of DNRA to total NO 3 − reduction can be particularly important in both estuarine sediments (∼5-91%; An and Gardner, 2002;Megonigal et al, 2004;Gardner et al, 2006;Burgin and Hamilton, 2007;Dong et al, 2009;Giblin et al, 2013;Roberts et al, 2014;Plummer et al, 2015;Kessler et al, 2019) and freshwater lake sediments (∼3-50%; Nizzoli et al, 2010;Wenk et al, 2014;Robertson and Thamdrup, 2017). Yet, the natural variability in these studied environments is quite high.…”
Section: Discussion Denitrification Versus Dnra In Lake Lugano Sedimentssupporting
confidence: 52%
“…Desulfobulbaceae include organisms known as cable bacteria that are capable of sulphur oxidation with either oxygen (Nielsen et al, 2010;Pfeffer et al, 2012) or nitrate (Marzocchi et al, 2014;Kessler et al, 2018Kessler et al, , 2019 as electron acceptors. In addition to their role as sulphide oxidizers, a recent study showed cable bacteria enhanced the relative importance of DNRA by increasing Fe 2+ availability (via decreasing the pH which allowed FeS dissolution) that promoted other microbes in the community to conduct Fe-dependent DNRA (Kessler et al, 2019). However, in our experiment, only one Desulfobulbaceae ASV, that had no assigned Genus using the Silva database, closely matched a cable bacteria genus (Candidate genus Electrothrix (Trojan et al, 2016)] [>95% identity, NCBI's nucleotide collection database (Agarwala et al, 2018)].…”
Section: Evidence Of Sulphide Oxidation Under High P Sulphidementioning
confidence: 99%
“…It has been suggested that when long filaments form, a chain of cells at the sulfidic terminal catalyzes anodic half reactions (e.g., 0.5 H 2 S + 2H 2 O → 0.5 SO 2− 4 + 4e − + 5H + ), while a cathodic half reaction (O 2 + 4e − + 4H + → 2H 2 O) is completed by cells at the oxic terminal. Electron transfer then occurs along the lon-gitudinal ridges of CB filaments via electron hopping promoted by extracellular cytochromes positioned within a redox gradient or via conductive electronic structures such as pili (Bjerg et al, 2018;Cornelissen et al, 2018;Kjeldsen et al, 2019;Meysman et al, 2019;Pfeffer et al, 2012). These hypotheses await further verification, and CB remain uncultured and difficult to grow outside of sediment.…”
Section: Introductionmentioning
confidence: 99%